Text Detection and Character Segmentation from Natural Scene Images Based Using Graph Cut Labeling (International Journal of Engineering and Computer Science, 2015)
This paper presents an innovative scheme for character detection and segmentation from natural scene images professionally. In detection juncture canny edge and sobel edge is employed. To detect the edges of the text and so that it is achievable to extract only the text regions and non text regions are filtered out by using some geometric properties of text.  For segmentation phase graph cut labeling technique is used for extracting characters from detective text regions rapidly.